Potential of Sorghum Polyphenols to Prevent and Treat Alzheimer’s Disease: A Review Article - Rezaee, Nasim; Fernando, W.M.A.D. Binosha; Hone, Eugene; Sohrabi, Hamid R.; Johnson, Stuart K.; Gunzburg, Stuart; Martins, Ralph N. (Frontiers in Aging Neuroscience, 2021)
Alzheimer’s disease (AD) is characterized by the excessive deposition of extracellular amyloid-beta peptide (Aβ) and the build-up of intracellular neuroﬁbrillary tangles containing hyperphosphorylated tau proteins. This leads to neuronal damage, cell death and consequently results in memory and learning impairments leading to dementia. Although the exact cause of AD is not yet clear, numerous studies indicate that oxidative stress, inflammation, and mitochondrial dysfunction significantly contribute to its onset and progression. There is no effective therapeutic approach to stop the progression of AD and its associated symptoms. Thus, early intervention, preferably, pre-clinically when the brain is not significantly affected, is a better option for effective treatment. Natural polyphenols (PP) target multiple AD-related pathways such as protecting the brain from Aβ and tau neurotoxicity, ameliorating oxidative damage and mitochondrial dysfunction. Among natural products, the cereal crop sorghum has some unique features. It is one of the major global grain crops but in the developed world, it is primarily used as feed for farm animals. A broad range of PP, including phenolic acids, flavonoids, and condensed tannins are present in sorghum grain including some classes such as proanthocyanidins that are rarely found in others plants. Pigmented varieties of sorghum have the highest polyphenolic content and antioxidant activity which potentially makes their consumption beneficial for human health through different pathways such as oxidative stress reduction and thus the prevention and treatment of neurodegenerative diseases. This review summarizes the potential of sorghum PP to beneficially affect the neuropathology of AD.